2020
DOI: 10.3390/molecules25092017
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Behavior of pH-Responsive Peptide A6K without End-Capping

Abstract: A short self-assembly peptide A6K (H2N−AAAAAAK−OH) with unmodified N− and C−terminus was designed, and the charge distribution model of this short peptide at different pH was established by computer simulation. The pH of the solution was adjusted according to the model and the corresponding self-assembled structure was observed using a transmission electron microscope (TEM). As the pH changes, the peptide will assemble into blocks or nanoribbons, which indicates that the A6K peptide is a pH-responsive peptide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…[26,27] Amino acids with an ionizable side chain, such as lysine or glutamic acid have been commonly selected and placed in a hydrophilic domain of a synthetic peptide to control the pH-dependent self-assembly process. [6,9,[28][29][30][31][32][33][34][35][36][37] In particular, recently it was discovered that by judicious selection of amino acid building blocks, pH-responsive peptides can form supramolecular nanostructures with various morphology. [38,39] Although there have been successful examples of pH-responsive peptide self-assembly, most systems require a custom-design approach through fine-balancing the number of acidic and basic residues in the solvent-exposed region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26,27] Amino acids with an ionizable side chain, such as lysine or glutamic acid have been commonly selected and placed in a hydrophilic domain of a synthetic peptide to control the pH-dependent self-assembly process. [6,9,[28][29][30][31][32][33][34][35][36][37] In particular, recently it was discovered that by judicious selection of amino acid building blocks, pH-responsive peptides can form supramolecular nanostructures with various morphology. [38,39] Although there have been successful examples of pH-responsive peptide self-assembly, most systems require a custom-design approach through fine-balancing the number of acidic and basic residues in the solvent-exposed region.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the mechanistic understanding of peptide self‐assembly further promote the development of hierarchical peptide self‐assembly with long‐range ordering [26,27] . Amino acids with an ionizable side chain, such as lysine or glutamic acid have been commonly selected and placed in a hydrophilic domain of a synthetic peptide to control the pH‐dependent self‐assembly process [6,9,28–37] . In particular, recently it was discovered that by judicious selection of amino acid building blocks, pH‐responsive peptides can form supramolecular nanostructures with various morphology [38,39] .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical strength of the pH 10 hydrogel was slightly reduced compared with that of the pH 7 hydrogel as revealed by the rheological results (Figure e,f). This is likely due to the partial breakage of nanofibers (Supporting Information, Figure S2) because the lysine-rich C 12 G 2 molecule is close to the isoelectric point at high pH with the results of charge screening …”
Section: Resultsmentioning
confidence: 99%
“…Based on the structure, the application value of surfactant‐like peptides can be explored. It was shown that surfactant‐like peptides with this structure have self‐assembly properties at different pH (Zhang et al, 2020). Moreover, as an antibacterial peptide, it showed antibacterial activity against Gram‐negative E. coli and Gram‐positive Staphylococcus aureus (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%